Cooperative binding of Sox10 to DNA: requirements and consequences - Wegner, Michael; et al. (Nucleic Acids Research, 2002)
The high-mobility-group (HMG) domain containing transcription factor Sox10 is an important regulator of various processes including the development of neural crest cells and glial cells. Target gene promoters contain multiple Sox10-binding sites, which either support monomeric or cooperative, dimeric binding. The latter is unusual for Sox proteins and might contribute to functional specificity of Sox10. We find that specific amino acid residues in a conserved region immediately preceding the HMG domain of Sox10 are required for cooperative binding. These residues cooperate with the HMG domain during dimeric binding in a manner dependent on specific determinants within the first two α-helices of the HMG domain. Cooperativity of DNA binding is surprisingly refractory to changes in the overall conformation of the DNA-bound dimer. Whereas maintenance of cooperativity is essential for full activation of the promoter of the myelin protein zero target gene, dimer-dependent conformational changes such as the exact bending angle introduced into the promoter appear to be less important, shedding new light on the architectural function of Sox proteins.
UnivIS-Import:2015-03-09:Pub.2002.med.IB.LPCIPDBI.cooper_1